Bone Formed After Maxillary Sinus Floor Augmentation by Bone Autografting With Hydroxyapatite and Low-Level Laser Therapy: A Randomized Controlled Trial With Histomorphometrical and Immunohistochemical Analyses. Issue 5 (October 2018) - Theodoro, Leticia Helena; Rocha, Gustavo Spina; Ribeiro Junior, Valmir Lucas; Sakakura, Celso Eduardo; de Mello Neto, João Martins; Garcia, Valdir Gouveia; Ervolino, Edilson; Marcantonio Junior, Elcio
Abstract : Purpose: The aim of this study was to evaluate the bone formed after maxillary sinus floor augmentation (MSFA) by bone autografting combined with hydroxyapatite (HA) that had been either treated with low-level laser therapy (LLLT) or not. Materials and Methods: Twelve biopsies were obtained from patients 6 months after MSFA using a combination of 50% of autogenous bone (AB) and 50% of HA (AB/HA group, n = 6) followed by LLLT (AB/HA-LLLT group, n = 6). The laser used in this study was gallium–aluminium–arsenide laser with a wavelength of 830 nm (40 mW; 5.32 J/point; 0.57 W/cm 2 ). Samples obtained were subjected to histological, histometric, and immunohistochemical analysis for detection of tartrate-resistant acid phosphatase and runt-related transcription factor 2. The data were submitted to statistical analysis (Shapiro–Wilk and Student t tests; α = 5%). Results: Statistical analysis revealed no significant difference in vital bone presence and immunohistochemical analysis between the groups. There was no reduction in bone marrow or fibrous tissue in the AB/HA group and AB/HA-LLLT group. There was a decrease in the amount of remaining biomaterial between the groups ( P = 0.0081). Conclusion: LLLT did not increase the formation of new bone; instead, it accelerated the bone remodeling process.